2020
DOI: 10.1002/cjoc.202000389
|View full text |Cite
|
Sign up to set email alerts
|

Initial Electrode Kinetics of Anion Intercalation and De‐intercalation in Nonaqueous Al‐Graphite Batteries

Abstract: Graphite electrode | Anion intercalation | Al battery | Electrochemical kinetics | Diffusion Graphitic materials with intercalated sites are considered as the mostly used positive electrode materials in nonaqueous Al batteries. Unlike the small-size cations, the intercalation/de-intercalation of large-size anions into/out of graphite would induce large volume expansion and micro-structure reconfiguration, leading to unexpected coulombic efficiency in the full cells (<95% within initial several cycles). For und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The experimental results also confirmed the practical diffusion coefficient of graphite electrode. The results indicate that the value could reach on the order of ∼10 –8 cm 2 s –1 in nonaqueous RABs, which would decrease with progressive AlCl 4 – anion intercalation …”
Section: Thermodynamics and Kinetics Of Rabsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results also confirmed the practical diffusion coefficient of graphite electrode. The results indicate that the value could reach on the order of ∼10 –8 cm 2 s –1 in nonaqueous RABs, which would decrease with progressive AlCl 4 – anion intercalation …”
Section: Thermodynamics and Kinetics Of Rabsmentioning
confidence: 99%
“…The results indicate that the value could reach on the order of ∼10 −8 cm 2 s −1 in nonaqueous RABs, which would decrease with progressive AlCl 4 − anion intercalation. 125 For 3D diffusion with geometry factor b of 6, the diffusion coefficient can be written as eq 32: 123…”
mentioning
confidence: 99%
“…Han et al. [ 66 ] determined that the selection of appropriate graphite powders could be an essential factor in influencing the electrochemical performance of Al‐graphite cells because the graphite size could fundamentally determine the kinetics of both mass transport in the electrolyte and diffusion ability in the graphitic layers.…”
Section: Recent Progresses Of Positive Materialsmentioning
confidence: 99%
“…À intercalation into the graphite matrix. [10,11] Han et al [12] compared the performance of four different graphite materials and concluded that graphite size affects the reversibility and kinetics of AlCl 4 À diffusion into graphite electrodes during intercalation/deintercalation processes. They claimed that graphite morphology influences the trapping, diffusion coefficient and mass transfer kinetics of AlCl 4 À intercalation/deintercalation into/from graphite.…”
Section: Introductionmentioning
confidence: 99%